Increased susceptibility of ethanol-treated gastric mucosa to naproxen and its inhibition by DA-9601, an Artemisia asiatica extract - Oh, Tae Young (World J Gastroenterol, 2005)
AIM: To examine the effect of DA-9601, a new gastroprotective agent, on the vulnerability of ethanol-treated rat’s stomach to naproxen (NAP). METHODS: Male Sprague-Dawley rats were pretreated with 1 mL of 50% ethanol twice a day for 5 d and then NAP (50 mg/kg) was administered. DA-9601 was administered 1 h before NAP. Four hours after NAP, the rats were killed to examine gross injury index (mm(2)), histologic change and to determine mucosal levels of malondialdehyde (MDA), prostaglandin E(2) (PGE(2)), glutathione (GSH) and myeloperoxidase (MPO). RESULTS: Pretreatment of ethanol significantly increased NAP-induced gastric lesions, as well as an increase in MDA and MPO. On the contrary, mucosal PGE(2) and GSH contents were decreased dramatically by ethanol pretreatment, which were aggravated by NAP. DA-9601 significantly reduced NAP-induced gastric injury grossly and microscopically, regardless of pretreatment with ethanol. DA-9601 preserved, or rather, increased mucosal PGE(2) and GSH in NAP-treated rats (P<0.05), with reduction in mucosal MDA and MPO levels. CONCLUSION: These results suggest that repeated alcohol consumption renders gastric mucosa more susceptible to NSAIDs though, at least in part, reduction of endogenous cytoprotectants including PGE(2) and GSH, and increase in MPO activation, and that DA-9601, a new gastroprotectant, can reduce the increased vulnerability of ethanol consumers to NSAIDs-induced gastric damage via the mechanism in which PGE(2) and GSH are involved.